Assessment of acid deposition in the Dhaka division of Bangladesh using air pollution dispersion modeling - Iqbal, Asif; Nguyen, Thi Kim Oanh; Annachhatre, Ajit P.; Shipin, Oleg V.; Iyngararasan, Mylvakanam; Thailand (HM Queen) (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Acid deposition stimulates the stressed environmental condition in large extent, as the soil become more acidic leading to decreased production and ecosystem imbalance. Assessment of acid deposition, in the form of dry and wet deposition is thus important to demonstrate the level of stress. The objective of the study is to assess the acid deposition in Bangladesh for the year 2006 considering both local emission and long range air pollution transport. The study analyzes the potential impacts of acid deposition in respect to the critical load of ecosystem for Bangladesh. The MM5-CAMx modeling system is used to assess the acid deposition over the Dhaka division of Bangladesh. In order to assess the acid deposition, an emission inventory is conducted for the brick kilns of Dhaka division. Emission inventory of 2000 is updated to 2006 considering the economic and sectoral developments in case of other contributing sectors. The CGRER database containing emissions in 1p0 (Bx 1p0 (Bresolutions is used for the large domain to incorporate into the model. 3-way nesting is done for meteorological processing using MM5 modeling system and 2-way nesting is used for CAMx model. HYSPLIT model is used to assess air mass trajectory coming into Bangladesh. The maximum annual average concentration of SOx and NOx is simulated as 25 ppb and 100 ppb respectively in Dhaka city of Bangladesh. The NOx value exceeds the annual standard for Bangladesh. The concentration profile shows the highest concentration zone along Dhaka city, where maximum brick kilns, industrial, residential and transportation activity takes place. In Dhaka division significant level of acid deposition takes place, about 0.66 kg/ha/yr and 6.2 kg/ha/yr in the form sulfur and nitrogen respectively. The sulfur deposition simulated is considerably lower than the critical load for the terrestrial ecosystem of Bangladesh, while nitrogen deposition rate is significantly higher. The simulated result expects potential threat to the terrestrial ecosystem of Bangladesh for the level of acid deposition and will create severe threat if not managed properly. Getting monitoring result all over the places is an expensive job, which can be done by the modeling conducted in this study in order to support the decision making process for sustainable environmental managements
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2009
Keywords: Air -- Pollution -- Evaluation -- Bangladesh